Business Objects companion - Jackson, David, 1948- (Prentice Hall, 1998)
With Business Objects software, thousands of companies are transforming their databases into powerful end-user resources for competitive advantage. Now, there's a hands-on guide to deploying, managing and optimizing Business Objects for maximum impact: Business Objects Companion. Whether you're using Business Objects as a standalone DSS tool, or along with SAP, Baan, or PeopleSoft, you'll find this book invaluable. You'll discover administration techniques that maximize control while giving your users all the flexibility they need. You'll learn how to integrate Business Objects with your Excel worksheets, querying databases directly from Excel and incorporating the results automatically.